Upaya Meningkatkan Minat Belajar Siswa Dengan Model Pembelajaran Kooperatif Tipe Picture And Picture Di SD Negeri Miritpetikusan - Hasanah, Uswatun; Khoiriyah, Zulfah Uswatun; Fatimah, Siti; Subarkah, Imam (IAINU Kebumen, 2022)
The role of the Picture And Picture Cooperative learning model in providing solutions to problems faced by students at SD Negeri Mirit Petikusan (a case study at SD Negeri Petikusan). This research is based on the traditional learning method which focuses on the lecture method, does not involve active students, is very detrimental to students in receiving lessons, passive students tend to be busy talking to other friends alone, 60% of students pay attention to the rest do not pay attention to learning in class well, sleepy and bored and some students do not want to do assignments on PAI subjects. The purpose of this study was to find out the results of the Picture and Picture Cooperative Learning Model to add interest in learning, especially for 6th grade elementary school students in PAI subjects, this research focused on the Picture and Picture Cooperative Learning Model in fostering student interest in teaching and learning activities. PAI learning. This type of research is a case study field research, data collection techniques using Observation, Interview and Documentation methods. The data analysis technique uses Miles and Huberman analysis with a sequence of steps for data reduction, data presentation and data verification. The results of this study indicate that (1) the implementation of learning using the Picture and Picture Cooperative Learning Model is very liked by students because it is more fun and also not monotonous like using the lecture method which makes students feel bored quickly and don't even pay attention to the lesson (2) the use of the Picture and Picture Cooperative Learning Model was successful in growing students' interest in learning PAI.Keywords: Picture and Picture Cooperative Learning Model, Interest in learning